Adaptasi Tradisi Kearifan Pesantren dalam Pendidikan Modern - Zuyyina Candra Kirana (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
The background of writing this article is that there are still many assumptions that education in Islamic boarding schools is a form of backwardness in the midst of the progress of the times, whereas in reality if you look at the field the products in Islamic boarding schools are not inferior to other education. So the author wants to provide a portrait of Islamic boarding school wisdom that must be imitated and adapted in formal education as an effort to find solutions to problems from various gaps in the form of violence, morality and character building towards an intelligent, inclusive and wise society. Pesantren not only teach religious understanding, but are also able to see religion based on its context, and still prioritize the values ​​of local wisdom. Kiai as a leader in the pesantren always provides knowledge and values ​​that can be realized in life. Islamic boarding schools teach to adapt to cultural variants by not leaving the pesantren culture. The adaptation of the pesantren education system in the modernization era is the adjustment of the pesantren education system to the modern system method, namely the adjustment of traditional system methods in the current modernization era. Adaptation of the pesantren education system means the use of learning methods that can be accepted from all students and with a novelty system, Islamic boarding schools are not easy to throw away with old culture or learning method systems such as wetonan, bandongan and so on, Islamic boarding schools continue to take the old method and also have the development role by taking the current system or method in accordance with the times. From here, Islamic boarding schools can adapt according to the conditions of Islamic boarding schools in the modernization era.